EFFECT OF WASTE ENGINE OIL ON PROXIMATE, PHYTOCHEMICAL, AND ANTIBACTERIAL CONSTITUENTS OF Teffairia Occidentalis (PUMPKIN LEAF) - Atuanya, E. I.; Sunday, E.; Aso, Rufus E. (FUDMA JOURNAL OF SCIENCES, 2024)
The improper disposal of waste engine oil effluent onto gutters, open lands, and cultivated farm lands is a common practice in Nigeria, especially among mechanics. These effluents contain substances derived from hydrocarbons that can diminish soil fertility and also influence the properties of plants. This study was consequently undertaken to examine the effects of waste engine oil on the nutritional, phytochemical, and antibacterial constituents of Telfairia occidentalis (Pumpkin leaf). Various levels (0ml, 100ml, 200ml, 300ml, and 400ml) of diesel oil contamination were mixed with 2 kilograms (kg) of soil, with each treatment replicated three times. Plants were watered daily for four months, and after 16 weeks, leaf samples were collected for laboratory analysis. The nutritional composition, phytochemical properties, and antibacterial components of the leaves were examined. The results indicated a significant reduction (P<0.05) in protein (12±0.02), fats (7±0.02), ash (15±0.25), fiber (10±0.03), and carbohydrate (10±0.25) content in the 400ml waste oil treatment compared to the control (0ml) values (protein: 38±0.01, crude fat: 25±0.13, total ash: 45±0.07, crude fiber: 36±0.15, carbohydrate: 42±0.04). Phytochemical analysis demonstrated a noteworthy decrease in alkaloids, saponins, flavonoids, and phenols as waste oil levels increased in the soil, compared to the control (0ml). The antibacterial activity screening revealed that among the various concentrations (80mg/ml, and 20mg/100 ml) of extracts studied, 80g/ 100 ml showed the highest degree of inhibition on all the test organisms. However, there was a notable reduction in inhibition as the level of waste oil pollution increased in the soil, compared to the control...